The Politico-divine will of the founder of Islamic Republic of Iran, Imam Khomeini, peace be upon him [soundrecording]. (Tehran, Iran The Institute for Compilation and Publications of the works of Imam Khomeini peace be upon him)
An English translation of the late Imam Khomeini's last will.
Keywords: Khomeini, Ruhollah; Iran -- Politics and government -- 1979-1997.; Islam; Koran; Religion; Public speaking; Political science